Goldenhar Syndrome associated with Vestibular Fistula and Esophageal Atresia - A Rare Association - Dinesh Kumar Barolia; Sunil Kumar Mehra; Vinita Chaturvedi; Guruddat Raipuria; Aditya Pratap Singh; Abhishek Kumar Rai (EL-Med-Pub, 2018)
Goldenhar syndrome is associated with various other congenital anomalies of gastro-intestinal tract, heart, kidney and genitourinary system. We report a rare association of Goldenhar syndrome with vestibular fistula and esophageal atresia.